Sistem Pemantauan Tempat Sampah Pintar Berbasis IoT dengan Jaringan NB-IoT - Emilia Julita Kadja; Menhya Snae (Jurnal Manajemen Informatika & Teknologi, 2025)
The Smart Trash Can Monitoring System aims to create an automated solution for monitoring and managing trash can conditions. The method used in this system is IoT-based smart trash can monitoring technology, which utilizes ultrasonic sensors to measure the height of the trash and proximity sensors to detect objects around the trash can. The sensor data is processed by Node Mcu. There are 2 bins for organic and non-organic waste. Each of them is installed with one capacitive proximity sensor and one inductive proximity sensor. If the user detects organic waste in the right bin with a distance of less than 10 cm, the system will drive the servo motor to open the bin cover, and send a message to Telegram. In addition, if the height of the garbage exceeds the threshold, the system sends a notification to Telegram. The result of implementing this system has the potential to increase the efficiency of waste collection and create a healthier environment.